A comprehensive approach to optimizing malaria prevention in pregnant women: evaluating the efficacy, cost-effectiveness, and resistance of IPTp-SP and IPTp-DP - Sarah-Leah Eisenberg; Adam E. Krieger (Taylor & Francis Group, 2023)
Malaria during pregnancy is a major global health concern, with approximately 10,000 pregnant women dying from malaria-related anaemia each year. The World Health Organization has suggested intermittent preventive treatment with sulphadoxine-pyrimethamine (IPTp-SP) to avert malaria infection in pregnant women in malaria-endemic areas, but this intermittent preventive (IP) treatment is at risk of becoming ineffective due to parasite resistance and the contraindication in HIV-infected women. This paper argues that alternative IP treatments such as dihydroartemisinin-piperaquine (DP) should be explored, alongside the urgent need to investigate antimalarial cycling strategies. Additionally, the cost-effectiveness of IPTp-DP should be evaluated, as well as potential barriers to IP treatment such as medication stockouts, late attendance at antenatal clinics, lack of autonomy and freedom among women, and lack of knowledge about malaria prevention. Health education focusing on malaria prevention should be incorporated into routine antenatal care programmes to improve patient compliance. A comprehensive approach that includes the administration of IPTp-DP alone along with other measures such as insecticide-treated nets and medical education is the key to addressing the devastating effects of malaria infection in pregnant women.